ANALISIS STATISTIK TELEKOMUNIKASI DAN PENDIDIKAN DI INDONESIA TAHUN 2022 DAN 2023 - Harahap, Sarwedi; Ritonga, Zon Saroha (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
This research analyzes telecommunication and education statistical data in Indonesia for the years 2022 and 2023, obtained from the publications of the Central Statistics Agency (BPS). The study aims to understand the trends in the use of information and communication technology and the condition of education in Indonesia post-COVID-19 pandemic. The data analyzed includes internet usage, mobile phone usage, educational facilities and infrastructure, school participation, as well as the outcomes and achievements of the educational process. The analysis results show a significant increase in access to information and communication technology, reflecting the efforts of the government and the private sector in expanding digital infrastructure. However, this research also reveals various challenges in the education sector that still need to be addressed, including disparities in access to technology in remote areas, the quality of educational facilities and infrastructure that still needs improvement, and the need to enhance the capacity of teachers and educational staff. Therefore, to achieve sustainable development, holistic and inclusive policies are needed, focusing not only on increasing technology access but also on improving the overall quality of education. This research provides essential insights for policymakers in formulating effective strategies to address these challenges and strengthen the education system in Indonesia.